New Visions of Nature
XIX, 285 p.
Keywords: Contemporary visions of nature have been deeply affected by the ongoing interaction and interpenetration of science, nature, and society. These new visions appear to be more complex than older visions of nature and at the same time they seem to challenge our notions of authenticity. "New Visions of Nature" focuses on the emergence of these new visions of complex nature in three domains. The first selection of essays reflects public visions of nature, that is, nature as it is experienced, encountered, and instrumentalized by diverse publics. The second selection zooms in on micro nature and explores the world of contemporary genomics. The final section returns to the macro world and discusses the ethics of place in present-day landscape philosophy and environmental ethics. The contributions to this volume explore perceptual and conceptual boundaries between the human and the natural, or between an ‘out there’ and ‘in here.’ They attempt to specify how nature has been publicly and genomically constructed, known and described through metaphors and re-envisioned in terms of landscape and place. By parsing out and rendering explicit these divergent views, the volume asks for a re-thinking of our relationship with nature.